Characterization of peptide mimics to antigens chaperoned by Hsp70 in MDA-MB-231 breast tumour cells - Arnaiz Villanueva, Blanca Esther (Trinity College (Dublin, Ireland). Department of Microbiology, 2005)
Tumour-derived heat shock protein (Hsp) preparations have been shown to elicit anti-tumour immune responses in both mice and man. Analysis of Hsp preparations from tumour cells revealed that the immuno-protective property resides with the peptides complexed with Hsps (Hsp-PCs). Clinical trials are on going using autologous Hsp extracts as a source of antigens to boost immune responses against tumours. The advantage of this vaccine is that no prior knowledge of the tumour antigens associated with Hsps is required. The disadvantages are that it is patient-dependent and requires invasive surgery.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin